2016
DOI: 10.1039/c6ta04657f
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic and photovoltaic properties of the air-stable organohalide semiconductor (CH3NH3)3Bi2I9

Abstract: A lead-free and air-stable organohalide semiconductor exhibiting noteworthy optoelectronic properties is investigated. With improvements in thin film processing, this material is expected to yield good solar cell efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
130
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 48 publications
18
130
0
Order By: Relevance
“…Figure 1 shows the structure of MABI determined by single-crystal diffraction measured at room temperature 24 . The materials show hexagonal symmetry ( P 6 3 / m m c ) and the face-shared BiI 6 bioctahedra or (Bi 2 I 9 ) 3− clusters are separated by CH 3 NH 3 + groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the structure of MABI determined by single-crystal diffraction measured at room temperature 24 . The materials show hexagonal symmetry ( P 6 3 / m m c ) and the face-shared BiI 6 bioctahedra or (Bi 2 I 9 ) 3− clusters are separated by CH 3 NH 3 + groups.…”
Section: Resultsmentioning
confidence: 99%
“…An analogous explanation on the even poorer performance compared to the 2D layered perovskite could be the enhanced confinement of charge carriers, but this explanation has not been elucidated because the performance of a solar cell depends on multiple parameters, such as the band energy alignment of different components and the microstructure of the layers. In a more recent study, MABI shows a double-peak emission including one close to band gap coupled with one in the blue light region and is superior in stability over lead-based perovskite in ambient air 23, 24 . Interestingly, long-lived excitons on the scale of nanoseconds have also been observed, which contrasts with the low performance of devices based on MABI 23, 24 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other than molecular metal halide species, metal halide clusters containing multiple metal atoms can also serve as the building block to assemble 0D metal halide hybrids. For example, (CH 3 NH 3 ) 3 Bi 2 I 9 was first reported by Kawai et al in 1990s [136] and has recently emerged as a possible candidate as light absorber [137][138][139]. Smith et al reported the synthesis of a family of sulfonium-based lead bromide hybrids consisting of Pb 3 Br 12 6− trimers [140].…”
Section: D Metal Halide Hybridsmentioning
confidence: 99%
“…They calculated an exciton binding energy of 300 meV, which is much larger than the exciton binding energy of 5 meV reported for CH 3 NH 3 PbI 3 . 54 Abulikemu et al 55 reported the synthesis of (CH 3 NH 3 ) 3 Bi 2 I 9 single crystals from reaction precursors in concentrated HI, with recrystallization from an anti-solvent. An indirect bandgap of 1.96 eV was determined, although the excitonic nature of the material was not considered in the bandgap measurement.…”
Section: A Single Crystalsmentioning
confidence: 99%